Development of interactive multimedia based on problem-based learning in grade V elementary school - Deni, Aden Nopriyan; Suratmi, Suratmi (Universitas Ahmad Dahlan, 2024)
The use of media plays a crucial role in the learning process to achieve learning objectives. However, the utilization of instructional media is still not optimal because it often overlooks the characteristics and needs of learners. Leveraging digital technology can be one of the solutions to address this issue. This research aims to produce interactive multimedia based on problem-based learning on the human digestive system in class V elementary school. The research method used is Research and Development (R&D) with research procedures using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects used were class V students for the 2023/2024 academic year, totaling 20 students. The data collection techniques used were interviews, validation sheets, and questionnaires. The data obtained was analyzed quantitatively and descriptively. The results of research through a validation process by material experts, media experts, and practitioners show that interactive multimedia based on problem-based learning is very suitable for use in the learning process in elementary schools. The results of field trials show that interactive multimedia based on problem-based learning is very practical to use as a learning medium to convey material on the human digestive system in elementary schools. The conclusion of this research is that the resulting PBL-based interactive multimedia product is very feasible and practical for learning in class V elementary schools.